2021
DOI: 10.1149/1945-7111/abd44b
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Substituents in Fluorinated Cyclic Carbonates in the Performance of High Voltage Lithium-Ion Battery Electrolyte

Abstract: Ethylene carbonate (EC) has been used as the Solid-Electrolyte Interphase (SEI) former in the conventional electrolyte for decades. However, its low anodic stability leads to severe capacity decay during cycling under high voltage operation. Therefore, finding a viable electrolyte with high anodic stability and the ability to form robust SEI for high voltage lithium-ion batteries is of primary importance. In this study, a series of electrolytes containing various fluorinated cyclic carbonates as the SEI former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
0
23
0
1
Order By: Relevance
“…As shown in Figure S17, Supporting Information, the Nyquist plots of batteries charged to 4 V at different cycles are composed of a semicircle in the high frequency, a semicircle at medium frequency and a straight line at low frequency, corresponding to the interface impedance of CEI layer, the charge transfer resistance and the Warburg impedance, respectively. [16,23,24] After the first cycle, the CEI layer impedance and charge transfer resistance are basically similar in reference electrolyte system (R s : 22.83 Ω; R ct :53.87 Ω) and β-carotene-containing electrolyte system (R s : 31.36 Ω; R ct :49.26 Ω), indicating that the introduction of additives has little influence on the viscosity and conductivity of the electrolyte. However, with the increase of cycles, the impedance values of the two systems have changed dramatically.…”
Section: Analysis Of the Cathode And Electrolyte After Cyclesmentioning
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure S17, Supporting Information, the Nyquist plots of batteries charged to 4 V at different cycles are composed of a semicircle in the high frequency, a semicircle at medium frequency and a straight line at low frequency, corresponding to the interface impedance of CEI layer, the charge transfer resistance and the Warburg impedance, respectively. [16,23,24] After the first cycle, the CEI layer impedance and charge transfer resistance are basically similar in reference electrolyte system (R s : 22.83 Ω; R ct :53.87 Ω) and β-carotene-containing electrolyte system (R s : 31.36 Ω; R ct :49.26 Ω), indicating that the introduction of additives has little influence on the viscosity and conductivity of the electrolyte. However, with the increase of cycles, the impedance values of the two systems have changed dramatically.…”
Section: Analysis Of the Cathode And Electrolyte After Cyclesmentioning
confidence: 90%
“…Higher Mn content in the reference electrolyte system is due to the dissolution of transition metals on the cathode side at high voltage, which may be reduced to products such as MnF 2 , Mn, or MnO at the anode side. [23] But in the β-carotene-containing electrolyte system, no significant amount of Mn was observed on the anode side because of the protective layer formed by the additives. It can be observed from TEM images that the protective layer with uneven surface distribution in the reference electrolyte cannot play a protective role (Figure S15, Supporting Information).…”
Section: Analysis Of the Cathode And Electrolyte After Cyclesmentioning
confidence: 98%
“…He et al compared the oxidation potentials of different fluorinated solvents with linear sweep voltammetry, and the results showed that most of the systems replaced by fluorinated solvents had better antioxidant capacity than the common EC/EMC systems. [62] The HOMO level of sulfoxide solvents is also lower than that of conventional carbonate solvents. Moreover, it has higher electrochemical stability, which is attributed to the more electronegativity of sulfonyl group than carbonyl group, resulting in an electrochemical window of more than 5 V. Sulfone solvents have strong interactions with lithium salts to achieve high conductivity, and have lower combustibility than carbonate solvents, so they are a promising high-voltage solvent.…”
Section: High-voltage Electrolyte Solventmentioning
confidence: 99%
“…He et al compared the oxidation potentials of different fluorinated solvents with linear sweep voltammetry, and the results showed that most of the systems replaced by fluorinated solvents had better antioxidant capacity than the common EC/EMC systems. [ 62 ]…”
Section: Different Electrolyte Modification Strategies Improve High‐v...mentioning
confidence: 99%
“…As discussed above, the effect of fluorination, including the aforementioned units on cyclic carbonate molecules [ 26 , 27 ], linear ethers [ 28 ], and other molecules on the LIB electrolytes, were investigated at the same time; the first-principles calculation was performed to study fluoride electrolytes for sodium-ion batteries [ 29 , 30 , 31 , 32 ]. However, limited studies have focused on the systematic design of fluoride electrolytes for SIBs based on the -CF 1 , -CF 2 , and -CF 3 units for the two types of solvent molecules.…”
Section: Introductionmentioning
confidence: 99%